Investigating SO2 transfer across the air-water interface via LIF - Friman, Sonja I.; Jähne, Bernd (Experiments in fluids, 2019)
A laser-induced fluorescence technique to measure vertical concentration profiles of the tracer sulfur dioxide above the air-water interface is presented. The imaging technique is capable of recording profiles at a rate of up to 40 Hz with a sufficiently high spatial resolution to resolve the profile within the viscous boundary layer in the air at the air-water interface. The new technique was tested in a small wind-wave facility under invasion conditions with an initial concentration of 100 ppm in the air at estimated wind speeds u10u10u_{10} of 0.7-3 m/s, corresponding to friction velocities between 2.4 and 9.3 cm/s. The laser used for fluorescence excitation has a wavelength of 223.7 nm. In this work, a proof of principle is presented as well as a first evaluation of the capabilities and uncertainties of the technique. The new technique enables a detailed study of the transport processes in the air-sided boundary layer at a wavy interface including the gas transfer velocity, turbulent concentration fluctuations, and the partitioning of gas transfer between air and water.Graphical abstract Open image in new window
Gesehen am 10.04.2019
Im Titel ist „2“ tiefgestellt